Methodological approach to evaluation the level of a university organizational culture - E. V. Kotov; Yu. O. Roschina (Вестник университета, 2022)
The authors propose a methodological approach to quantitative assessing the level of organizational culture of a university of a humanitarian profile. This assessment methodology was tested on scientific and pedagogical workers who took part in an expert survey. The results of an expert interview are given in the article. Not only employees of humanitarian universities, but also employees of universities of a natural and technical profile, having education in the field of social (humanitarian) sciences acted as experts. The purpose of the study was to identify the features and patterns in the formation and implementation of the organizational culture of the university of humanitarian profile. The authors propose an original methodology, which allows assessing the level of organizational culture simultaneously from three positions – past, present and future (desired) state. The level of organizational culture is determined on the basis of an integral (generalizing) indicator, which, unlike analogues developed by other researchers, is calculated as the geometric mean of the integral indexes of groups of indicators, which makes it possible to determine the median value, which is the closest to the average value.